AN ENHANCEMENT LEADERSHIP MANAGEMENT TO IMPROVE TEACHING PERFORMANCE - Ulpah Maisari; Atma Jonar Asih; Ridwan Syahputra; Juniar Juniar; Ely Ezir (SEAN Institute, 2023)
Principal Managerial Model in Improving Student Character at elementary school Medan. The purpose of this research is to find out how the model, results, inhibiting factors, and supporters of the principal's managerial in improving student character at SD Panca Budi Medan, using qualitative methods of observation, interviews, field notes, and documentation, which were conducted for 4 months from January-April 2019. The results of the principal's managerial model in improving student character at elementary school Medan are management of how to carry out his role as principal, synergizing an educational ecosystem that creates a culture and work climate, organizing a comfortable, beautiful and clean school physical environment, fostering an efficient, creative, and innovative work culture. for renewal to achieve the goal of improving the character of honesty, caring, queuing, confidence, and discipline of students at elementary school Medan as a cultured education of quality and quality character.